Desafíos de la gobernanza del agua en América Latina: una perspectiva biopolítica - Ramos, Fernando (2024)
Despite the abundant water resources in Latin America, severe disparities in distribution and access persist, necessitating a comprehensive examination of water governance practices. This paper aims to critically analyze the challenges and complexities of water governance in Latin America through a biopolitical perspective. The analysis reveals that water governance is profoundly influenced by historical inequalities, neoliberal policies, and sociopolitical power structures. The study concludes that effective water governance requires a holistic and integrated approach that addresses the biopolitical dimensions of resource management. This necessitates centralized coordination, enhanced subnational capacities, and prioritization of vulnerable populations to achieve sustainable and equitable water governance.